Assess the knowledge regarding the use of menstrual cups among B.Sc. Nursing students in Upasana College of Nursing Kollam - Salini Sasikumar, (International Journal of Nursing Research, 2025)
Background: The study to assess the knowledge regarding the use of menstrual cups among B.Sc Nursing students in Upasana College of Nursing Kollam. The objective of this study is to assess the knowledge regarding the use of menstrual cups among B.Sc Nursing students to find out the association between the Knowledge of B.Sc Nursing with selected demographic variables. Materials and Methods: The approach used in this study is non-experimental and the research design is qualitative. The sample consists of 30 students from the 4th semester B.Sc. Nursing students in Upasana College of Nursing, Kollam. The instrument used in the study is a structured questionnaire, after obtaining consent, a structured knowledge questionnaire was given to them. The data were collected and analyzed using descriptive and inferential statistics techniques. Results: Research which revealed that 36.6% of students have good knowledge, 56.6% have average knowledge, and 6.67% have poor knowledge regarding the use of menstrual cups and there is a significant association between knowledge score and area of residence, there is no significant association between age, religion, monthly family income, exposure to health-related information, source of health-related information, type of family and monthly expenditure for sanitary products. Conclusion: Menstrual cups are a better alternative to the current methods of menstrual sanitation, and it is durable, eco-friendly, comfortable, safe, has no need for frequent changing in the day, and has no disposal issues.